Supernumerary eumorphic mandibular incisor in association with aggressive periodontitis - Verma Vikas; Goel Amit; Mohd. Sabir (Wolters Kluwer Medknow Publications, 2010)
According to the literature, the prevalence of supernumerary teeth is 1% to 4% of permanent dentitions; and among these, the presence of fifth mandibular incisor - a supernumerary eumorphic tooth - has rarely been described in literature, and its association with localized aggressive periodontitis is an even more rare entity. This paper reports a very rare case of unusual association of supernumerary eumorphic fifth mandibular incisor with aggressive periodontitis in a Muslim individual, so that these findings generate curiosity and inspire others to carry out further studies and investigations.